Pengenalan Dasar English Morphology Melalui Materi Conjuction Bagi Siswa MTS Swasta di Kota Palangka Raya - Hapsari, Muliana Setia; Qamariah, Zaitun; Widiastuty, Hesty (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to introduce basic English morphology through the teaching of conjunction materials to students in the private secondary school MTS Hidayatul Insan Palangka Raya. The importance of basic English morphology for these students prompted the selection of this topic. Teaching is conducted using an interactive approach involving discussions, exercises, and language games to reinforce students' understanding. The activity involves eighth-grade students as the main subjects, with evaluations conducted before and after the intervention to measure their improvement. Results show significant improvement in the correct use of conjunctions in sentences and a better understanding of simple sentence structures. Additionally, students demonstrated enthusiasm and active participation during teaching sessions, indicating increased interest in learning English. In conclusion, teaching conjunction materials with an interactive method proved effective in introducing basic English morphology to students at MTS Hidayatul Insan Palangka Raya.